2020
DOI: 10.3892/mco.2020.2090
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic pediatric severe familial adenomatous polyposis: A case report

Abstract: Familial adenomatous polyposis (FAP) is an autosomal dominant hereditary precancerous condition caused by germline pathogenetic variants in the tumor suppressor adenomatous polyposis coli (APC) gene. Patients with FAP develop multiple gastrointestinal adenomatous polyps usually at the age of ~20 years, which, if untreated, become cancerous in 100% of cases. Genotype-phenotype associations have been extensively described; however, inter-and intra-familial variability exists. It is crucial to characterize the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The mutation had occurred in a conserved amino acid position but it was predicted to be tolerated by SIFT and suggested to be benign by PolyPhen. In this respect, Picelli et al, 38 Cerasuolo et al, 39 and Fernández‑Rozadilla et al 40 concluded that it was not a disease causing variant because it was found equally distributed among normal and FAP‐affected individuals. Our analysis showed that only p. Arg653Met mutation is likely to have damaging and deleterious effects on the APC protein.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation had occurred in a conserved amino acid position but it was predicted to be tolerated by SIFT and suggested to be benign by PolyPhen. In this respect, Picelli et al, 38 Cerasuolo et al, 39 and Fernández‑Rozadilla et al 40 concluded that it was not a disease causing variant because it was found equally distributed among normal and FAP‐affected individuals. Our analysis showed that only p. Arg653Met mutation is likely to have damaging and deleterious effects on the APC protein.…”
Section: Discussionmentioning
confidence: 99%
“…Many germline pathogenic variants in each of these genes cause the diseases' onset, with penetrance varying according to the specific syndrome [17][18][19][20]. We demonstrated that quantitative alterations in the expression of the same genes contribute to generate inter-and intra-familial phenotypic heterogeneity [21,22]. Furthermore, germline pathogenic variants in specific gene, such as the phosphatase and tensin 106 homolog (PTEN) gene, generate constitutive beta-catenin and cytokine dysregulation, activating inflammatory pathways and, in turn, increasing cancer risk of carrier subjects [23].…”
Section: Crcs: Epidemiology and Geneticsmentioning
confidence: 99%
“…In humans, when germline variants likely associated with a certain disease are observed in patients, it is possible to examine their close relatives, such as parents and siblings, relatively easily to determine whether the disease is transmitted in association with the candidate DNA variant within the family. For example, while more than 3000 different germline APC variants causing FAP have been identified [ 17 ], novel pathogenic APC variants have still been discovered in recent studies in which examinations of family members were conventionally performed [ 18 , 19 , 20 , 21 ]. In contrast, it is challenging to trace the relatives of household dogs after disease onset.…”
Section: Introductionmentioning
confidence: 99%